Analisis dampak penerapan sistem pengelolaan perkakas berbasis paradigma Industry 4.0: Studi kasus industri padat karya - Laulia Ariyani Rangkuti; Sri Raharno (Jurnal Teknik Mesin Indonesia, 2022)
In general, production orders will not be completed according to the production schedule if there are obstacles in the production process, such as damaged production machines, material shortages, lack of operators and poor tool management. Solution for this problem, namely tool management, is to use the industry 4.0 paradigm through the development of a cyber physical system. Cyber physical system concept for the tool management system is carried out by giving identity to all tools. At the time the tool will be distributed, the tool must first be scanned using hardware. Through this scanning process, data is obtained in the form of the number of tools that have been distributed and available. The tool availability data is not only used to control tool distribution but also very influential in determining tool requirements plans. The next step after designing a tool management system is to analyze the impact that occurs from the application of a tool management system applied to a labor-intensive industry. The method applied in this analysis is the collection and analysis of current conditions and then compared with conditions that will occur as a consequence of implementing the system. In addition, an analysis of the need for the application of a tool management system is also carried out in terms of hardware requirements and systems for data processing.